Good vibrations? An investigation examining the effects of speed, tyre pressure and wheel choice on whole-body vibration during road cycling - Dixon, W. (Journal of Science and Cycling, 2023)
Whole-body vibration and hand-arm vibration can be detrimental to health leading to numerous musculoskeletal disorders among other issues. The aim of this study was to investigate the effects that speed, tyre pressure and wheel choice had on whole-body vibration (WBV) and hand-arm vibration (HAV) while road cycling. With added analysis provided by the implementation of a power spectral density (PSD). The study was performed around a 1-kilometre loop on varying road surface by one participant. The wheelsets used were provided by Hunt Wheels (Hunt 48 and Hunt 34); each of these were tested at speeds of 20,30, and 40 kilometres per hour (kph), each at a pressure of 60,70,80 and 90 pounds per square inch (psi). Each combination was repeated 7 times. The bike was fitted with six accelerometers to record the vibration; rear hub, saddle and lumbar to measure WBV; front hub, handlebar, and left wrist to measure HAV. The recorded data was then processed using custom MATLAB script to calculate the average exposure over an eight-hour day (A(8)) and the fourth-power vibration dose value (VDV) outlined in ISO-2631. Additionally, a PSD of the vibration was plotted using Welch`s Method which the max power, the frequency where the maximum occurred, and the absolute power were extracted. The VDV occupational limit was exceeded at all speeds with both tyre pressure (p>0.075) and changing wheelsets (p > 0.793) having no significant effect on reducing the value at the rear hub. The A(8) limit value was not passed and the time to reach it was over 3 hours at 40 kph. The max power and absolute power both increased with speed with the wheelset having no significant effect (p>0.108), however pressure did have significant effect, but only between 60 psi and higher pressures at lower speeds. The frequency at which the max power occurred at the lumbar was between 2.77-5.48 Hz which aligns with the destructive frequency of the lower back. WBV while cycling surpasses the occupational limits and changing speed, tyre pressure and wheelsets has no effect on reducing it to safe levels. Further research into products advertised to reduce vibration while cycling would be beneficial to the cycling community.